(3SajfI GdLhbs - (3eMeO Ndjd GdSeQLjs
(3ChdgG (B:s
(3ef Yed GdfhGgO hGdQbe ddCOjH eMeO GdSeQLi GdTeS ef aQW GdMSO ef JhGQJ HGdMLGH hNOgG GdZGfi YbO Sbjb QhV ai GdTHGH s
(3BNQgG (B:s
(3Ef TQH GdjeHG jOGhi hjHOi HgG bHjM s
(3eLehYI JhGTM Ydi JQJjH GdZGfi ai GdhRGf YdjgG NGJe GdecJHI HJGQjN (B1314 (3g`s
(3HBNQg YHGQI (B: (3ebOeI NGOece MGaX cJH TjN GdESdGe GHQGgje Hf eMeO MeOi hNGJeg HJGQjN (B1315 s
(3hHChdgG agQS ddCTYGQ ai KdGK hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B289s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B90 s
Keywords: (3GdCOHs